Treatment of Hepatitis C Post-Liver Transplantation Could Mitigate Discard Rates of Hepatitis C-Positive Deceased Donor Livers and Expand the Donor Pool - Jennifer Keller; Gary Marklin; Obi Okoye; Roshani Desai; Tej Sura; Ajay Jain; Chintalapati Varma; Mustafa Nazzal (Journal of Transplantation)
Background. Prior to 2014, treatment for hepatitis C was limited. However, the subsequent introduction of direct acting antiviral medications (DAA) against hepatitis C led to improvements in morbidity and better medication tolerance. DAA therapy allowed for an increase in treatment rates of hepatitis C in patients on the liver transplant waiting list. With the popularization of DAA, there became a growing concern about the utility of hepatitis C-positive (HCV+) deceased liver donors, especially after treating HCV+ potential recipients on the transplant waiting list. Methods. This is a retrospective, observational study using Mid-America Transplant Services (MTS) database from 2008 to 2017. Comparison was made before the widespread use of DAAs 2008–2013 (pre-DAA) against their common practice use 2014–2017 (post-DAA). All deceased liver donors with HCV antibody or nucleic acid positive results were evaluated. Results. Between 2008 and 2017, 96 deceased liver donors were positive for HCV. In the pre-DAA era, 47 deceased liver donors were positive for HCV, of which 32 (68.1%) were transplanted and 15 (31.9%) were discarded. In the post-DAA era, a total of 49 HCV+ organs were identified, out of which 43 (87.8%) livers were transplanted and 6 (12.2%) were discarded. Discard rate was significantly higher in the pre-DAA population (31.9% vs. 12.2%, p = 0.026). Secondary analysis showed a distinct trend towards increased regional sharing and utilization of HCV+ donors. Conclusion. In order to reduce discard rates of HCV+ patients, our data suggest that transplant centers could potentially delay HCV treatment in patients on the transplant waitlist.